Targeting the undruggable in pancreatic cancer using nano-based gene silencing drugs. (May 2020) - Kokkinos, John; Ignacio, Rosa Mistica C.; Sharbeen, George; Boyer, Cyrille; Gonzales-Aloy, Estrella; Goldstein, David; Australian Pancreatic Cancer Genome Initiative (APGI),; McCarroll, Joshua A.; Phillips, Phoebe A.
Abstract: Pancreatic cancer is predicted to be the second leading cause of cancer-related death by 2025. The best chemotherapy only extends survival by an average of 18 weeks. The extensive fibrotic stroma surrounding the tumor curbs therapeutic options as chemotherapy drugs cannot freely penetrate the tumor. RNA interference (RNAi) has emerged as a promising approach to revolutionize cancer treatment. Small interfering RNA (siRNA) can be designed to inhibit the expression of any gene which is important given the high degree of genetic heterogeneity present in pancreatic tumors. Despite the potential of siRNA therapies, there are hurdles limiting their clinical application such as poor transport across biological barriers, limited cellular uptake, degradation, and rapid clearance. Nanotechnology can address these challenges. In fact, the past few decades have seen the conceptualization, design, pre-clinical testing and recent clinical approval of a RNAi nanodrug to treat disease. In this review, we comment on the current state of play of clinical trials evaluating siRNA nanodrugs and review pre-clinical studies investigating the efficacy of siRNA therapeutics in pancreatic cancer. We assess the physiological barriers unique to pancreatic cancer that need to be considered when designing and testing new nanomedicines for this disease.